2011
DOI: 10.1523/jneurosci.1097-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Templates in Visual Working Memory

Abstract: Most theories of attention propose that we maintain attentional templates in visual working memory to control what information is selected. In the present study, we directly tested this proposal by measuring the contralateral-delay activity (CDA) of human event-related potentials (ERPs) during visual search tasks in which the target is cued on each trial. Here we show that the CDA can be used to measure the maintenance of attentional templates in visual working memory while processing complex visual scenes. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

49
433
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 340 publications
(509 citation statements)
references
References 44 publications
(71 reference statements)
49
433
3
Order By: Relevance
“…Consistent with the facilitatory VWM-based effects observed by Chelazzi and colleagues (1998;Chelazzi et al, 1993), search distractors capture attention (i.e., increase search times) to a greater extent when they resemble the content of VWM representations Soto et al, 2008). Of most relevance to the present study are investigations using ERPs that have clarified when target templates are stored in VWM and when other memory systems are used, such as long-term visual memory (Carlisle et al, 2011;. Using the contralateral delay activity (CDA) as an index of VWM activity (Vogel & Machizawa, 2004), Carlisle and colleagues demonstrated that the contribution of VWM in the maintenance of the target template dissipates quickly during variable searches, in which the identity of the target changes across trials.…”
Section: Vwm-based Facilitation During Visual Searchsupporting
confidence: 88%
See 2 more Smart Citations
“…Consistent with the facilitatory VWM-based effects observed by Chelazzi and colleagues (1998;Chelazzi et al, 1993), search distractors capture attention (i.e., increase search times) to a greater extent when they resemble the content of VWM representations Soto et al, 2008). Of most relevance to the present study are investigations using ERPs that have clarified when target templates are stored in VWM and when other memory systems are used, such as long-term visual memory (Carlisle et al, 2011;. Using the contralateral delay activity (CDA) as an index of VWM activity (Vogel & Machizawa, 2004), Carlisle and colleagues demonstrated that the contribution of VWM in the maintenance of the target template dissipates quickly during variable searches, in which the identity of the target changes across trials.…”
Section: Vwm-based Facilitation During Visual Searchsupporting
confidence: 88%
“…This previous study only employed a static search target (i.e., the letter BH^), a condition in which the search target template should be maintained in long-term memory (Carlisle et al, 2011). The primary purpose of Experiment 1 was to replicate the paradigm of AlAidroos et al with a variable search target, to test whether the signature of VWM-based inhibition would continue to be observed when VWM was also used to maintain the target template.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The activity of neurons in inferior temporal cortex (IT) that selectively respond to a particular object is enhanced in a sustained fashion while monkeys prepare to find this object in an upcoming search display (Figure 3a), and such preparatory "baseline shifts" of neural activity level may reflect an activated attentional template [7]. Similar target-selective preparatory activation patterns have been found in human event-related brain potential (ERP) and fMRI experiments [8][9][10][11][12][13][14]. Some fMRI studies have demonstrated increased activity in colour-or motion-selective visual areas when observers prepare for targets defined in these dimensions [9][10][11].…”
Section: Preparationmentioning
confidence: 54%
“…For example, in the typical memory-based capture paradigm [5,6], colour is not a defining feature of the visual search target, yet a match to a colour actively maintained in VWM reliably captures attention. Olivers et al [21] argued that in these cases, the target feature is constant across many trials, and the search template is offloaded to long-term memory [34]. In the absence of a task-relevant search template in VWM, other items in VWM are automatically 'promoted' to an active state and influence selection, acting as a template.…”
Section: Discussionmentioning
confidence: 99%